Laser Direct Writing of Silver Clusters‐Based Subwavelength Periodic Structures Embedded in Mid‐Infrared Gallo‐Germanate Glass. Issue 10 (29th May 2022) - Guérineau, Théo; Fargues, Alexandre; Lapointe, Jerome; Vallée, Réal; Messaddeq, Younès; Canioni, Lionel; Petit, Yannick; Cardinal, Thierry
Abstract : The direct laser writing (DLW) using femtosecond lasers allows for the inscription of 3D microstructures embedded inside optical materials. Based solely on the silver ions photochemistry, the DLW in silver‐containing glasses enables to locally induce inside glasses a unique combination of optical properties. The physical modifications of the material encompass not only a refractive index change, but also new physical properties like fluorescence, second‐ and third‐harmonic generations, and surface plasmon resonance. Numerous efforts are deployed to develop the DLW‐assisted silver photochemistry in phosphate glasses. However, this glass family is suffering from its near‐infrared optical cutoff as opposed to the silver‐doped gallo‐germanate glasses. With an extended mid‐infrared (mid‐IR) transmission, these glasses are synthesized via the melt‐quenching technique. Depending on the glass composition, either a glass matrix‐based single track (Type I) or a silver cluster‐based double track (Type A) of refractive index change is produced. By enabling an order of magnitude smaller structures than with Type I, Type A modification is further expanded to embed, for the first time, periodic structures below the inter‐track spacing. Demonstrated with a pitch down to 400 nm, these Type A–based periodic structures bring new insights through the fabrication of 3D diffractive gratings in mid‐IR glasses. Abstract : Herein, the silver‐assisted direct laser writing in mid‐infrared transmitting gallo‐germanate glasses is demonstrated. Via a careful optimization of the glass composition, a sub‐micrometric photoinduced glass modification is produced. Based on this phenomenon, 3D periodic structures are fabricated inside the glass volume. The present findings pave the way for the fabrication of subwavelength‐integrated components in mid‐infrared devices.